2013
DOI: 10.1007/s11060-013-1107-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of IDH mutation in adult low-grade gliomas: a meta-analysis

Abstract: Mutations in the gene encoding isocitrate dehydrogenase (IDH) have been identified in approximately 65-90 % of low-grade gliomas (LGGs). Various studies examining the relationship between IDH mutation with the clinical outcome in patients with LGGs have yielded inconclusive results. The purpose of the present meta-analysis of literature is to determine this effect. We conducted a meta-analysis of 10 studies (937 patients) that evaluated the correlation between IDH mutation and overall survival (OS). For the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…Regarding the survival analysis, previous studies demonstrated the prognostic significance of IDH1 mutations (Arita et al., 2015; Brennan et al., 2013; Ducray et al., 2011; Hartmann et al., 2010; Killela et al., 2014; Lewandowska et al., 2014; Mellai et al., 2011; Olar et al., 2012; Parsons et al., 2008; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011; Sun et al., 2013; Takano et al., 2012; Weller et al., 2009). Some authors observed that OS and PFS in IDH mutated cases were about twice longer than in wild‐type patients (Arita et al., 2015; Polivka et al., 2014), and others showed that mutation in IDH1 was an independent factor for a favorable prognosis (Brennan et al., 2013; Ducray et al., 2011; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the survival analysis, previous studies demonstrated the prognostic significance of IDH1 mutations (Arita et al., 2015; Brennan et al., 2013; Ducray et al., 2011; Hartmann et al., 2010; Killela et al., 2014; Lewandowska et al., 2014; Mellai et al., 2011; Olar et al., 2012; Parsons et al., 2008; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011; Sun et al., 2013; Takano et al., 2012; Weller et al., 2009). Some authors observed that OS and PFS in IDH mutated cases were about twice longer than in wild‐type patients (Arita et al., 2015; Polivka et al., 2014), and others showed that mutation in IDH1 was an independent factor for a favorable prognosis (Brennan et al., 2013; Ducray et al., 2011; Polivka et al., 2014; Sanson et al., 2009; Shibahara et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic factors predicting survival of gliomas patients can help us not only get a better understanding of the pathogenesis of brain tumors but provide much help in choosing optimal treatment for patients. Currently, there are a number of biomarkers identified as prognostic factors in brain tumors, such as isocitrate dehydrogenase mutations and matrix metalloproteinase 9 expression [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…33 This strong association between LGGs and IDH mutation has several diagnostic implications. The first is the plausible hypothesis that IDH1-mutant GBMs represent malignant transformation of undiagnosed LGGs, and IDH1 wild-type GBM is, in many ways, a different disease sharing the same histological features.…”
Section: Diagnostic and Prognostic Implications Of Idh Mutationmentioning
confidence: 99%
“…A meta-analysis of 937 patients showed that among patients with LGG, those whose lesions had IDH mutation had a more favorable prognosis (pooled hazard ratio [HR] of 0.585, p = 0.025) compared with IDH wild-type LGGs. 33 In the NOA-04 trial of 318 patients with anaplastic glioma, multivariate analyses also showed that IDH1 mutation was an independent prognostic factor that conferred a longer progression-free survival (PFS) irrespective of the treatment received, and this effect was statistically greater than the risk reduction seen with 1p19q codeletion, MGMT promoter methylation, or histological features. 39 Conversely, the absence of IDH mutation in an intermediate-or even low-grade glioma portends a potentially worse prognosis than that of a GBM that has IDH mutation.…”
Section: Diagnostic and Prognostic Implications Of Idh Mutationmentioning
confidence: 99%
See 1 more Smart Citation